2009
DOI: 10.1038/sj.bjc.6604976
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Frizzled-related protein-1 is a negative regulator of androgen receptor activity in prostate cancer

Abstract: Secreted Frizzled-related protein-1 (sFRP1) associates with Wnt proteins and its loss can lead to activation of Wnt/b-catenin signalling. It is frequently downregulated in cancer, including prostate cancer, but its function in prostate cancer is unclear because it can increase proliferation of prostate epithelial cells. We investigated the function of sFRP1 in androgen-dependent prostate cancer and found that sFRP1 inhibited androgen receptor (AR) transcriptional activity. In addition, sFRP1 inhibited the prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 70 publications
2
40
0
Order By: Relevance
“…SFRP1 was reported as downregulated both in prostate cancer and cell lines 88 . Kawano et al 77 found SFRP1 as a negative regulator of the androgen receptor but this was mediated via neither canonical nor known non-canonical Wnt pathways. A physical interaction of SFRP1 with Frizzled receptors was found and a novel, so far uncharacterized pathway which might be shared with Wnt5a, has been suggested 77,89 .…”
Section: Wnt Signaling Abnormalities In Human Prostate Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…SFRP1 was reported as downregulated both in prostate cancer and cell lines 88 . Kawano et al 77 found SFRP1 as a negative regulator of the androgen receptor but this was mediated via neither canonical nor known non-canonical Wnt pathways. A physical interaction of SFRP1 with Frizzled receptors was found and a novel, so far uncharacterized pathway which might be shared with Wnt5a, has been suggested 77,89 .…”
Section: Wnt Signaling Abnormalities In Human Prostate Cancermentioning
confidence: 99%
“…Kawano et al 77 found SFRP1 as a negative regulator of the androgen receptor but this was mediated via neither canonical nor known non-canonical Wnt pathways. A physical interaction of SFRP1 with Frizzled receptors was found and a novel, so far uncharacterized pathway which might be shared with Wnt5a, has been suggested 77,89 . The role of SFRP1 may depend both on cell and receptor specific context as Joesting et al 90 reported elevated expression of SFRP1 in fibroblasts derived from prostate cancer stroma.…”
Section: Wnt Signaling Abnormalities In Human Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…SFRP1 can function as a negative regulator of the AR [120]. However, this effect of sFRP1 was not associated with Wnt inhibition [120]. Joesting et al [121] found that sFRP1 was overexpressed in prostate cancer stromal cells and ovexpression of sFRP1 activated JNK pathway, but not the canonical Wnt pathway.…”
mentioning
confidence: 99%
“…The sFRP family member sFRP1 was also found to be down-regulated both in prostate cancer tissues and prostate cancer cell lines. SFRP1 can function as a negative regulator of the AR [120]. However, this effect of sFRP1 was not associated with Wnt inhibition [120].…”
mentioning
confidence: 99%